Ubiquity of Legal Pluralism and its Consequences - Tamanaha, Brian Z (Victoria University of Wellington Law Review, 2024)
This article is a lightly edited version of the keynote address delivered at the 2023 ICON•S Annual Conference, held at Victoria University of Wellington—Te Herenga Waka, on 5 July 2023. I provide an overview of legal pluralism and its implications, addressing why legal pluralism heretofore has been overlooked by jurists, the historical roots of legal pluralism, how to identify what qualifies as law, internal and external legal pluralism, three categories of law that help frame legal pluralism, why customary law is difficult to incorporate within state law, the implications of legal pluralism for legal development and human rights, and much more.